Visualizing the impact of COVID-19 on PM2.5 concentrations in China. Issue 1 (1st January 2021) - Tang, Zhipeng; Mei, Ziao; Sui, Guangjun; Zou, Jialing
ABSTRACT: In response to the outbreak of COVID-19, the Chinese government imposed stringent lockdown measures to minimize the spread of the disease. This paper shows that under these measures, the PM2.5 concentrations were lower in February 2020 than in February 2019. However, after the measures were removed, the PM2.5 concentration returned to the same level as in the previous year, thus implicating that the reduction was temporary.